Effects of a dipole‐like crustal field on solar wind interaction with Mars. Issue 1 (20th February 2020) - Li, ShiBang; Lu, HaoYu; Cui, Jun; Yu, YiQun; Mazelle, Christian; Li, Yun; Cao, JinBin
Abstract : A three‐dimensional four species multi‐fluid magnetohydrodynamic (MHD) model was constructed to simulate the solar wind global interaction with Mars. The model was augmented to consider production and loss of the significant ion species in the Martian ionosphere, i.e., H +, O2 +, O +, CO2 +, associated with chemical reactions among all species. An ideal dipole‐like local crustal field model was used to simplify the empirically measured Martian crustal field. Results of this simulation suggest that the magnetic pile‐up region (MPR) and the velocity profile in the meridian plane are asymmetric, which is due to the nature of the multi‐fluid model to decouple individual ion velocity resulting in occurrence of plume flow in the northern Martian magnetotail. In the presence of dipole magnetic field model, boundary layers, such as bow shock (BS) and magnetic pile‐up boundary (MPB), become protuberant. Moreover, the crustal field has an inhibiting effect on the flux of ions escaping from Mars, an effect that occurs primarily in the region between the terminator (SZA 90°) and the Sun–Mars line of the magnetotail (SZA 180°), partially around the terminator region. In contrast, near the tailward central line the crustal field has no significant impact on the escaping flux.